Community Recognition of Child Marriage Practices: A Case in Indonesia - Amany, Rana Gyazki; Sultan, Sultan; Syam, Ridwan (Indonesian Journal of Social Science Research, 2023)
This study aims to determine the form of community recognition of the practice of child marriage that still takes place today in Bulu Cindea Village, Pangkajene and Islands Regency, Indonesia. This research contributes to analyzing the occurrence of child marriage practices that still continue. A qualitative research approach with a case study strategy was used to explore the case at the research location. The research informants were 11 people consisting of parents who have children who marry underage, children who marry underage and community leaders who know information about child marriage. The results of this study found that in the practice of child marriage there are three forms of recognition, namely: family recognition, recognition of community leaders, and recognition of government officials. Family recognition, the community views that this is the right decision because there are no negative impacts, needs and desires are fulfilled. Recognition from community leaders, there are still those who conduct underage marriages because of the cultural factors that they still hold strong. Recognition from government officials that underage marriage is commonplace, even this is due to customary factors or community understanding that is still taboo so that religious courts also have the authority to carry out marriage dispensation so that someone gets benefits and benefits and there are conditions that must be met.